ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI AUDIT GOING CONCERN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2017 – 2021) - Tamara Purnama T Sitanggang; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2023)
This study aims to analyze and describe the effect of Profitability, Liquidity, Leverage, Company Size, Audit Quality, and Audit Lag on Going concern Audit Opinions in Manufacturing Companies listed on the Indonesia Stock Exchange for the period 2017 – 2021. One of the issues in Indonesia that is related with a going concern opinion, namely one of the transportation companies in Indonesia which received an unqualified opinion by the auditing KAP, but later went bankrupt. The opinion received should indicate that the company's condition is good, but in reality the company is in a bad condition. This study uses agency theory to generate the hypothesis to be tested. This study used a purposive sampling technique with certain criteria in sampling. According to the specified criteria, obtained 100 research samples for 5 consecutive years and used logistic regression analysis as a data analysis technique. The results of the study show that liquidity has a significant negative effect on acceptance of going concern audit opinions. Leverage and audit lag have a significant positive effect on acceptance of a going concern audit opinion. Meanwhile profitability, firm size, and audit quality have no significant effect on the acceptance of going concern audit opinion. The results obtained from the Nagelkerke R Square test were 69.6%. It can be concluded that there are 30.4% of other independent variables that influence the acceptance of going concern audit opinions, outside of the independent variables that have been tested in research.